2001
DOI: 10.1364/josab.18.001742
|View full text |Cite
|
Sign up to set email alerts
|

Optical pulse compression to 50 fs by use of only a spatial light modulator for phase compensation

Abstract: We experimentally demonstrate the generation of 5.0-fs optical pulses (2.5 J, 1-kHz repetition rate), using only a spatial light modulator for phase compensation. Pulse compression of the broadband pulse (500-1000 nm) from an argon-filled capillary fiber is achieved with a liquid-crystal spatial light modulator without any prechirp compensation. The output pulse width is found to be 4.1 fs by a fringe-resolved autocorrelator fitted with a transform-limited pulse and to be 5.0 fs by second-harmonic generation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…We previously demonstrated that a SLM phase compensator enables us to compress pulses to sub-5 fs by inputting individual orders of dispersion into a SLM. 1 In this Letter we report, for the f irst time to the best of our knowledge, a 1.56-optical-cycle, 3.4-fs pulse generation through a single hollow fiber and only a programmable SLM by phase feedback with a significantly improved M-SPIDER.…”
mentioning
confidence: 88%
“…We previously demonstrated that a SLM phase compensator enables us to compress pulses to sub-5 fs by inputting individual orders of dispersion into a SLM. 1 In this Letter we report, for the f irst time to the best of our knowledge, a 1.56-optical-cycle, 3.4-fs pulse generation through a single hollow fiber and only a programmable SLM by phase feedback with a significantly improved M-SPIDER.…”
mentioning
confidence: 88%
“…8,17 Phase shaping has also been used to correct optical aberrations in a beam's wavefront, 18 and in femtosecond pulse shaping where phase compensation can lead to shorter pulse durations. 19 To improve the SLM for experiments demanding better resolution, it may be desirable to obtain a more expensive projector with a higher pixel density LCD. An alternate approach is to expand the laser beam so that it encompasses a larger number of pixels.…”
Section: Graduate Experiments: Holography and Optical Vorticesmentioning
confidence: 99%
“…There have been some experiments reported on ultrabroadband-pulse generation using a silica fiber 1,2) and an Ar-gasfilled hollow fiber, 3) and optical pulse compression by nonlinear chirp compensation. 1,3) For these experiments on generating few-optical-cycle pulses, characterizing the spectral phase of ultrabroad-band pulses analytically as well as experimentally is highly important.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, Kalosha and Herrmann considered the linear dispersion with two resonant frequencies and the nonlinear terms without the Raman effect. 6) For the single-cycle pulsegeneration experiment, we must use at least the shortest pulse of 3.4 fs 10) or sub-5 fs 3,11) or 7.1 fs 1) or the commercially available 12 fs pulses. Such a time regime is comparable to the Raman characteristic time of 5 fs 4) in a silica fiber.…”
Section: Introductionmentioning
confidence: 99%